Implementation of the Discovery Learning Model to Improve Learning Outcomes Basketball Dribbling Skills Students of Smk Negeri 1 Lamongan - Ahmad Efendi; Muhammad Muhammad; Tri Hadi Purnama (Universitas Majalengka, 2023)
The lack of interest of students at SMK Negeri 1 Lamongan in learning basketball dribbling is because the methods used during the learning process tend to be boring, causing their learning outcomes to be low, so it is necessary to use innovative learning models to improve learning outcomes for basketball dribbling. This research aims to improve the PJOK learning outcomes of students at SMK Negeri 1 Lamongan, especially basketball dribbling material, by applying the discovery learning model. This research is a type of classroom action research (PTK). The method used in this research uses the method initiated by Kemmis and McTaggart, where in carrying out the research there are several stages, namely planning, implementation, observation, and reflection. The instrument used in this research was a basketball dribbling skills test sheet. Based on the state of the research that has been done, the researcher conducted three research cycles. After each cycle experiences improvement, it can be concluded that the application of the discovery learning model can improve PJOK learning outcomes in basketball dribbling skills material. This increase was proven in cycle 3 to have learning completeness reaching 100% on all indicators.